Captain George Vancouver and British Columbia’s First Play - Hoffman, James (Theatre Research in Canada / Recherches théâtrales au Canada, 2000)
In June, 1790, in the midst of politically charged debates in Britain over the tiny trading port of Nootka Sound, on the west coast of what is now called Vancouver Island, a play opened in London that performed events both in the colony and at home—as the country prepared for war with Spain. In this article, I trace the historical and theatrical context of the staging of Nootka Sound; Or, Britain Prepar’d at the Theatre Royal, Covent Garden. Creatively using the possible attendance of George Vancouver at the opening performance, I consider the ambivalent role this production played in the hegemonic operations of Empire in the late eighteenth century. Appearing centrally within the imperial dramatic apparatus, it nonetheless contained considerable doubt and dissent, even anti-colonial assertion. In its direct engagement with both the locale and the politics of the west coast, I make a case for calling Nootka Sound; Or, Britain Prepar’d British Columbia’s first play. En juin 1790 en Bretagne, en plein milieu des débats politiques à propos du commerce du petit port de Nootka Sound, sur la côte ouest de ce qu’on appelle aujourd’hui l’Ile de Vancouver, et pendant que le pays se préparait à la guerre contre l’Espagne, se jouait à Londres la première d’une pièce qui mettait en scène les événements coloniaux et domestiques. Dans cet article je souligne les aspects historiques et théâtraux de la mise en scène de Nootka Sound; Or, Britain Prepar’d au Théâtre Royal, Covent Garden. Imaginant l’assistance de Georges Vancouver à la première, j’ai pensé à l’ambivalence du rôle qu’a joué la mise en scène sur les opérations hégémoniques de l’empire à la fin du xviiiè siècle. Se plaçant au centre de la machine dramatique impériale, cette pièce fut, dans un certain sens, un véhicule du désaccord et même du sentiment anti-colonialiste. Dans son engagement directe avec la vie locale et la politique de la côte ouest, j’ai plaidé la cause pour reconnaître Nootka Sound; Or, Britain Prepar’d comme la première pièce de la Colombie Brittanique.